PENERAPAN COLLABORATIVE WRITING UNTUK MENINGKATKAN KETERAMPILAN KERJASAMA DAN MOTIVASI MAHASISWA PADA MATA KULIAH PENULISAN KARYA TULIS ILMIAH - Astuti Wijayanti (LP2M Universitas Sarjanawiyata Tamansiswa, 2016)
This classroom action research deals with the implementation of collaborative writing in Scientific Writing subject. This research aims to describe how collaborative writing can be used to improve thecollaborative skill and motivation among the students of Natural Science Education Department. It was conducted in the Natural Science Education Department of the Faculty of Teachers Training and Education of Sarjanawiyata Tamansiswa University for six months. The number of subject is 37 students. The researcher used observation sheets including lecture observation sheet, students’ activity observation sheet used to know the implementation of collaborative writing, cooperative observation sheet used to know the cooperation among students and questionaire used to know students’ motivation after the implementation of collaborative writing. The research reported that there was an improvement of students’ cooperation in every cycle. Besides, it was also shown that there was an improvement of students’ motivation in cycle I from 87.8% to 87% in cycle II. Meanwhile, the average score of students’ writing also increased from 80.5 in cycle I to 84.2 in cycle II.Keywords: collaborative writing, motivation, cooperation